Seasonal Growth, Reproduction, and Health of the Pacific Oysters Cultured in an Intertidal Rack System in Garorim Bay, West Coast of Korea - Hee-Jung Lee; Jong-Won Park; Jeong-Ho Lee; Kwang-Sik Choi; Hyun-Ki Hong (Fishes, 2026)
This study investigated seasonal variation in tissue growth, reproductive status, energy reserves, and digestive tubule condition in the Pacific oyster, Magallana gigas, cultured in an off-bottom intertidal rack system in Garorim Bay on the west coast of Korea. Monthly samples of adult oysters were collected from February 2009 to December 2010. Condition index (CI), total carbohydrate content, reproductive stage, female reproductive effort estimated by indirect enzyme-linked immunosorbent assay (ELISA), and digestive tubule atrophy (DTA) were measured concurrently in individual oysters. Gametogenesis was largely synchronized between sexes and was strongly associated with seasonal sea surface temperature (r=0.84, p